2008
DOI: 10.4321/s1130-01082008000700002
|View full text |Cite
|
Sign up to set email alerts
|

Influencia de la especialización del cirujano en los resultados tras cirugía por cáncer de colon: Utilidad de los índices de propensión (propensity scores)

Abstract: INTRODUCCIÓNLa influencia del factor cirujano en los resultados quirúrgicos ha sido analizada de manera reiterada y para diferentes tipos de cáncer en la literatura científica mundial (1,2). El cáncer de colon no ha sido una excepción y mu- RESUMENIntroducción: la influencia del factor cirujano en el cáncer colorrectal se ha estudiado de manera reiterada en literatura científi-ca, pero los resultados han sido contradictorios. Se plantea en este estudio si la especialización del cirujano es un factor determina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…Propensity matching has been well described, but one of the weaknesses of this technique is that propensity scores tend to overestimate treatment effects because of survivor bias—only those patients contributing to the risk prediction model are those that survived to undergo treatment. 33,34 Rather than propensity score matching, we used logistic regression models using the Dartmouth-Manitoba claims-based modification of the Charlson comorbidity index. This methodology, although limited in the extent of clinical precision, has been validated broadly in surgical and nonsurgical settings.…”
Section: Discussionmentioning
confidence: 99%
“…Propensity matching has been well described, but one of the weaknesses of this technique is that propensity scores tend to overestimate treatment effects because of survivor bias—only those patients contributing to the risk prediction model are those that survived to undergo treatment. 33,34 Rather than propensity score matching, we used logistic regression models using the Dartmouth-Manitoba claims-based modification of the Charlson comorbidity index. This methodology, although limited in the extent of clinical precision, has been validated broadly in surgical and nonsurgical settings.…”
Section: Discussionmentioning
confidence: 99%
“…Most studies that have analyzed the influence of these physician-/center-related factors, particularly volume, on the variability of the process and outcome of cancer surgery are retrospective (7) and based on clinical-administrative databases (8). This explains why the most frequently examined outcome is hospital mortaliManagement and outcomes in digestive cancer surgery: design and initial results of a multicenter cohort study M This fact could explain the differences observed in some prospective studies with primary data (which enable the inclusion of a greater number of variables and have follow-ups which extend beyond the hospital period), in which the relationship between volume and outcomes is less consistent (8,9).…”
Section: Introductionmentioning
confidence: 99%